Trabecular metal monoblock versus modular tibial trays in total knee arthroplasty: meta-analysis of randomized control trials - Safa Abulhail (14150334) (2022)
Purpose Total knee arthroplasty is one of the significantly evolving procedures with different knee designs available in the market. The continued development of these prosthesis resulted in improvement of the implant survivorship and patient satisfaction. This study is an RCT-based meta-analysis aimed to compare two designs of total knee replacement: the conventional modular and the monoblock trabecular metal tibial trays. Methods This meta-analysis was performed by a literature review according to the PRISMA guidelines. A detailed search of the English literature was done using the PubMed, Medline, CINAHL, Cochrane, Embase, and Google Scholar databases. Only randomized control trials were included in the analysis after ensuring homogeneity. RevMan V.5.0.18.33 (The Cochrane Collaboration, Copenhagen, Denmark) was used to perform the meta-analysis. Extracted outcome measures were Knee Society score, Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) score, survivorship, complication rate, and radiostereographic analysis. Results Seven randomized control trials with 635 patients were eligible for our analysis after they met our inclusion criteria. Three hundred twelve patients received monoblock tibias, and the other 323 patients received modular tibial trays during their total knee arthroplasty surgeries. There were statistically significant superiority of the modular knees in the functional Knee Society and WOMAC scores at five years (P = 0.003 and 0.05, respectively). The modular design was also more stable on RSA at two years (P < 0.0001). Conclusion Modular and monoblock tibial trays are comparable knee designs with comparable survivorship and complication rates. However, the modular knees had better mid-term functional outcome and are more stable on radiostereographic analysis. Other Information Published in: International Orthopaedics License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s00264-022-05553-4